Whose Voice? Tim Crouch’s The Author and Active Listening on the Contemporary Stage - Vicky Angelaki (Sillages Critiques)
The essay discusses Tim Crouch’s recent play The Author (2009) in the context of active listening, audience participation, response and responsibility in contemporary theatre. It provides a critical engagement with the spectatorial experience of the piece so as to problematize the multiple uses of the physical medium of voice and speech in a contemporary play that delivers a fresh angle to narrativity and metatheatricality. At the same time, the essay probes the varied range of possibilities but also realistic extent of audience involvement in the play, tracing its deep textual contingencies to produce an overall understanding of the equally rewarding and precarious interrelationship between performance piece and audience.